IDENTIFIKASI MODEL PEMBIAYAAN USAHA KECIL DAN MENENGAH OLEH LEMBAGA KEUANGAN MIKRO DI KABUPATEN JEPARA - Anam, A. Khoirul; Nahar, Aida (BBM (Buletin Bisnis & Manajemen), 2015)
AbstractThe development of Micro, Small and Medium Enterprises (SMEs) is determined by the presence of microfinance institutions (MFIs) that offer financing models are diverse. But on the other hand the diversity of models offered MFI financing has yet to be exploited. The objectives of the study was to identify the characteristics of business and financing needs of SMEs, as well as identifying financing models that fit the character of SMEs. The approach used in this research is descriptive qualitative research through a case study approach, the informants in this study were employees and managers are authorized to provide information on financing models. While the research conducted in the district of Jepara. Based on comparative models and characteristics of SME financing, MFI cooperative model provides relatively brief filing procedure with a low ceiling making it suitable for small and micro businesses. As for MFIs BPR models have the advantage in providing kinds of products are more varied and larger loan limit and interest rates varied so suitable for this type of small and medium enterprisesÂ Keywods: SMEs, MFIs, financing model.